(3GdEcdjds - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s
(3ChdgG (B:s
(3HGH eG LGA ai PcQ bUhQ Gdjef heG YGbdgG hCbOe TF bUQ YeQGf bGd GdMSf GdgePGfi Chd bUhQ Gdjef s
(3BNQgG (B:s
(3hcd aQO jZdH jZdH eG ahbg ef aQO heG JMJg ef RhL GfJgi s
(3jdjgG cJGH (B"(3eYQaI GdZGdH hGdeZdhH(B" (3hGdWGdH hGdeWdhH JUfja GdMcje GQSWhWGdjS Ufag GdGScfOQ GdebOhfis
(3hhLO Pdc HBNQ GdLRA GdKGef ef GdEcdjd ai (B6 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B229 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B27 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs